2021
DOI: 10.18466/cbayarfbe.885696
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Asphalt Binder with Waste Expanded Polystyrene (EPS) Foam

Abstract: Waste polymers are widely used in asphalt modification, especially, in order to reduce their detrimental effect on the environment. This study discusses the usability of waste expanded polystyrene (EPS) foam in asphalt modification. In this respect, the EPS foam, which produces waste in both production and use stages, was mixed with bitumen by weight at the ratios of 2%, 4%, 6%, and 8%, and dry modification method was employed. The penetration, ductility, softening point, flash point, and specific gravity valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This specific condition causes the foam spongy but strong with a very lightweight property, resulting in efficient load-bearing and heat insulation. Recycling of that EPS foam can be applied in many ways e.g., admixture for the emulsion paint, admixture for the cement mortar, or modification of the asphaltic binder [3][4][5]. However, in the sense of Civil Engineering, the EPS foam can be used as a cohesive binder when it was dissolved in any suitable solvents e.g., acetone or toluene.…”
Section: Introductionmentioning
confidence: 99%
“…This specific condition causes the foam spongy but strong with a very lightweight property, resulting in efficient load-bearing and heat insulation. Recycling of that EPS foam can be applied in many ways e.g., admixture for the emulsion paint, admixture for the cement mortar, or modification of the asphaltic binder [3][4][5]. However, in the sense of Civil Engineering, the EPS foam can be used as a cohesive binder when it was dissolved in any suitable solvents e.g., acetone or toluene.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the addition of 1% EPS, by weight of total aggregate, the maximum EPS content they used, produced the maximum flash, fire, and softening points but the minimum ductility values. Yıldız et al [11] investigated modifying a base asphalt binder with waste EPS with ratios of 2%, 4%, 6%, and 8% (by weight of asphalt binder) and the following tests were applied to the modified binders: ductility, softening point, flash point, penetration and specific gravity. They found that increase in EPS content decreased the penetration and ductility values.…”
Section: Introductionmentioning
confidence: 99%